2018
DOI: 10.1073/pnas.1806296115
|View full text |Cite
|
Sign up to set email alerts
|

Elesclomol restores mitochondrial function in genetic models of copper deficiency

Abstract: SignificanceInherited pathogenic mutations in genes required for copper delivery to cytochrome c oxidase (CcO) perturb mitochondrial energy metabolism and result in fatal mitochondrial disease. A prior attempt to treat human patients with these mutations by direct copper supplementation was not successful, possibly because of inefficient copper delivery to the mitochondria. We performed a targeted search to identify compounds that can efficiently transport copper across biological membranes and identified eles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
66
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(71 citation statements)
references
References 31 publications
4
66
0
1
Order By: Relevance
“…For example, the copper ionophore elesclomol is an effective anticancer agent that causes oxidative damage to cancer cells by delivering toxic concentrations of copper to the mitochondria (81). More recently, however, low levels of elesclomol were seen to rescue copper deficiency in mammalian cells (82). We therefore tested whether PZ can also have both toxic and beneficial properties by addressing whether, at very low doses, it can rescue copper Figure 5.…”
Section: Pyrithione Zinc Effects On Secreted Sod5 and On C Albicans mentioning
confidence: 99%
“…For example, the copper ionophore elesclomol is an effective anticancer agent that causes oxidative damage to cancer cells by delivering toxic concentrations of copper to the mitochondria (81). More recently, however, low levels of elesclomol were seen to rescue copper deficiency in mammalian cells (82). We therefore tested whether PZ can also have both toxic and beneficial properties by addressing whether, at very low doses, it can rescue copper Figure 5.…”
Section: Pyrithione Zinc Effects On Secreted Sod5 and On C Albicans mentioning
confidence: 99%
“…Copper(I) released in the mitochondria can react with molecular oxygen generating ROS, which when produced in excess, can cause unmitigated oxidative stress and apoptotic death of cancer cells [14]. While this mechanism of action is consistent with its anticancer activity, it was recently shown that copper(I) released from elesclomol also becomes available for the metalation of CcO [8]. Consistently, low doses of elesclomol were shown to safely but effectively deliver copper to CcO and restore mitochondrial function in genetic models of copper deficiency [8].…”
Section: Elesclomol As a Copper-transporting Therapeutic Agentmentioning
confidence: 99%
“…This 'Trojan-horse' fashion delivery of metals by other lipophilic carrier molecules, such as the iron-transporting hinokitiol, has shown promise in restoring iron levels in preclinical animal models [7]. Using this principle, Soma et al, performed a targeted screen with a number of copper-binding pharmacological agents for their ability to restore respiratory growth in a yeast mutant defective in copper delivery to cytochrome c oxidase (CcO), a mitochondrial cuproenzyme [8]. This screen identified elesclomol as the most potent copper-transporting molecule, which rescued CcO function in a number of in vitro and in vivo models of copper deficiency [8,9].…”
Section: Rationalementioning
confidence: 99%
“…Accordingly, treatment of COA6-deficient patient fibroblasts with CuCl 2 revealed partial rescue of the observed COX levels [ 53 ]. Finally, the anticancer drug elesclomol (ES) was proposed to restore COX function by increasing mitochondrial copper content in patient cells with mutations in the COA6 and SCO2 proteins [ 47 , 55 ].…”
Section: Coa6 Is a Cox Assembly Factormentioning
confidence: 99%